A MULTILEVEL COMBINED MODEL OF USE RESTRICTION BASED ON MATRIX AND NEURAL NETWORKS - Kobiljanov Sh.N. (Innovate Conferences, 2026)
This in the article commerce banks information in systems use restriction process improvement Bell– LaPadula for the purpose and Biba security models combination based on working issued many level approach matrix and artificial neuron to networks based model offer Offer done method user and information security degrees mathematician vector and matrices using expression opportunity gives and this the process artificial intellect technologies using to automation conditions creates . Neuron network in the model user and information security degrees entrance parameters as taken away , hidden layer through permission to give or restriction decision is formed . As a result commerce banks information in systems of information confidentiality and integrity one at the time provision , as well as use management process flexibility and accuracy increase opportunity is created .
Keywords: information security, commerce banks, use limitation, Bell –LaPadula model, Biba model, neuron networks, matrix model, confidentiality, integrity, artificial intellect.